Roget's thesaurus of synonyms and antonyms - Roget, Peter Mark (United States of America : E. Kroiz, 1972)
Thesaurus English words and phrases I. Existence 2. Nonexcistence
Contenido I. Abstract relations II. Space III. Matter IV. Intellect V. volition VI. Affections
Keywords: ENCICLOPEDIA Y DICCIONARIOS; THESAURUS - SYNONYMS & ANTONYMS; TESAURUS SINONIMOS Y ANTONIMO